Construction and evaluation of a profile of professional competences in internal medicine - Análida Elisabeth Pinilla Roa (Universidad Nacional de Colombia, 2015)
The purpose of this research is to encourage the construction of professional profiles related to the health sciences, in particular, for internal medicine professionals, with the objective of providing them with tools to support their performance when facing the current challenges of their profession in Colombia and around the world. The professional competences that influence patient care are based on a socio-constructivist pedagogical approach, and is framed in a scientific, historical, normative, social and technological context.